THE POWER OF LAUGHTER: HUMOR, VIOLENCE AND CONSENSUS IN NEW SPAIN. 17TH AND 18TH CENTURIES - Lipsett-Rivera, Sonya (Revista de Historia Social y de las Mentalidades, 2016)
Joking and teasing permeated all aspects  of life in New Spain. Using court records  from Mexico City and its surrounding  communities, this article explores the ways  that laughter was deployed within New  Spain’s culture of masculinity. Humor was  both a means for to relate to each other but  also to mark differences. It was a normal  part of the day to day interactions of men  in New Spain between friends who joked  and teased but it could also fall flat when  one person did not have the right tone. Yet  the border between joking and insulting  comments was imprecise and thus often  led to conflicts. Laughter brought people  together when they were of the same social  class but when it was used in an offensive  manner, it was transformed into a weapon to  assert social distance. Such humor was also  part of seductions and similarly had political  overtones when it was used in satirical songs.  Humor brought people together and created  groups of insiders and outsiders. Laughter  was a powerful tool within social interactions  and provides an alternate way to understand  the culture of masculinity in colonial Mexico.
Keywords: Humor; Men; Friendship; Mexico; Tone; Satire; Songs